Dynamic relationship between young CEO and financial performance: a Malaysian perspective - Shafiq, Ume Salma; Selamat, Aslam Izah; Imam, Muhammad Asim; Hussain, Waleed; Khan, Muhammad Asif (Springer, 2026)
The role of young chief executive officers (CEOs) in firms’ financial performance is an interesting but controversial debate among scholars. This study investigates how young CEOs affect the financial performance of firms. Using panel data from 140 non-financial Malaysian firms listed on the Thomas Reuters Eikon database, we apply the generalized method of moments (GMM). The GMM results show a positive and significant relationship between young CEOs and financial performance in the studied samples. These findings have important implications for policymakers, who can enhance financial performance by developing and implementing policies that support young CEOs. This study validates the CEO–firm match theory in the Malaysian context, and these findings offer valuable insights for young CEOs on how to improve their financial performance by adopting good governance practices to address the firm’s challenges. The findings also have practical implications for the recruitment and selection of young CEOs in Malaysian firms.